The impact of CCT on driving safety in the normal and accident situation: A VR-based experimental study. (October 2021) - Li, Xiaojun; Ling, Jiaxin; Shen, Yi; Lu, Tong; Feng, Shouzhong; Zhu, Hehua
Highlights: VR application is extended to the investigation of CCT inside the tunnel. The effect of CCT on performance both in normal and accident cases is explored. Detailed validation of the proposed VR-based simulation method is conducted. Abstract: Correlated color temperature (CCT) of the light source inside the road tunnel plays a crucial role in ensuring driving safety, which is demonstrated by previous studies that CCT influences not only visual effects but also non-visual effects. Although conventional laboratory experiments could simulate the CCT environment inside the tunnel to some extent, they fail to restore driving experience, let alone simulate driving behavior in the accident situation. It has largely remained unclear whether and how CCT would influence visual/non-visual performance of the subjects who are performing driving tasks, especially in the accident situation. Motivated by this gap, a virtual-reality-based framework for assessing the influence of CCT on the visual and non/visual performance in normal driving situation and in accident situation was proposed. In this study, tunnel models under seven different CCTs were created and a rear-end accident was designed in the tunnel. By integrating analog driving equipment, all participants were required to perform virtual driving tasks both in the normal situation and in the accident situation. The non-visual performance (driving fatigue) and the visual performance (reaction time) of the participants were collected and analyzed. Results show that the CCT of light source inside the tunnel was significant on the driving fatigue of the driver who was performing driving task, and it also had a significant impact on the visual performance when the driver was faced with a rear-end accident. Detailed experimental methodology, behavioral explanations underlying these findings, validity of results and practical implications are also discussed in the paper.